Job stress among nurses in Ethiopia: A systematic review and meta-analysis - Woldu Aberhe; Teklewoini Mariye; Degena Bahrey; Abrha Hailay; Guesh Mebrahtom; Kidane Zereabruk; Guesh Gebreayezgi (Elsevier, 2024)
Background: Although job stress appears in all professions, jobs related to humans are associated with high levels of stress. Nurses are the most frequent medical staff who spend the largest amount of time with patients, cover all areas of the healthcare network, and experience serious job stress. To date, there have been no studies and protocols that estimated the pooled national prevalence of job stress among nurses in Ethiopia. Therefore, the primary purpose of this systematic review and meta-analysis is to determine the pooled national prevalence of job- related stress among Ethiopian nurses. Methods: Different database searching engines including PubMed, Scopus, Google Scholar, Africa journal Online, World Health Organization Afro library, and Cochrane review were systematically searched by using keywords such as "job-stress, occupational stress, work-related stress, job-related stress" and their combinations. Eight articles were finally selected with both published and unpublished observational studies that report the prevalence of job stress among nurses. The Preferred Reporting Items for Systematic Review and Meta-Analysis guideline was followed and, it is registered in the Prospero database (ID = CRD42020185450). Heterogeneity across the included studies was evaluated by the inconsistency index (I2). The random-effect model was fitted to estimate the pooled prevalence of job stress among Ethiopian nurses. All statistical analysis was done using R version 3.5.3 and R Studio version 1.2.5033 software for windows. Results: The pooled national prevalence of job stress among Ethiopian nurses was 49.6 % (95 % CI: 40.9, 58.3 %). This indicates that one out of two Ethiopian nurses had job stress. Based on subgroup analysis the prevalence of job stress among Amhara's and Oromia's region nurses was 44.9 % and 51.2 % respectively. Conclusion: The prevalence of job stress among Ethiopian nurses was high. Thus, our finding suggests that half of the Ethiopian nurses had job-related stress; therefore, managers, federal minister of health, and health policymakers should take effective measures and develop programs to reduce the prevalence of job stress among nurses.